PGAM1: a potential therapeutic target mediating Wnt/β-catenin signaling drives breast cancer progression - Yongxuan Wang; Wei Liu; Xudong Lai; Haixiong Miao; Xifeng Xiong (Discover Oncology)
Abstract Phosphoglycerate mutase 1 (PGAM1) has been identified as a key player in the progression and metastasis of various human cancer types, including breast cancer (BC); however, its precise oncogenic mechanism remains unclear. The present study aimed to investigate the oncogenic mechanisms of PGAM1 and establish its potential as a therapeutic target. Comprehensive analyses from the Tumor Immune Estimation Resource 2.0 and The Cancer Genome Atlas databases revealed a significant upregulation of PGAM1 in BC, correlating with poor clinical outcomes. Additionally, elevated expression of PGAM1 was confirmed in clinical BC samples. Silencing PGAM1 with specific small hairpin RNA in BC cells resulted in a marked reduction in cell proliferation, invasiveness and migration, alongside increased apoptosis and cell cycle arrest. In vivo experiments using tumor-bearing nude mice demonstrated that PGAM1 knockdown significantly reduced tumor volume and weight, effectively inhibiting tumor growth. Mechanistic investigations suggested that PGAM1 promoted BC tumorigenesis through the activation of the Wnt/β-catenin signaling pathway, both in vitro and in vivo. Therefore, the upregulation of PGAM1 in BC enhances malignancy via the Wnt/β-catenin signaling pathway, highlighting PGAM1 as a promising therapeutic target for BC treatment.